Proceedings of the Second International Conference on Computational Intelligence and Informatics ICCII 2017 (Advances in Intelligent Systems and Computing,, 2018)
The volume contains 69 high quality papers presented at International Conference on Computational Intelligence and Informatics (ICCII 2017). The conference was held during 25-27, September, 2017 at Department of Computer Science and Engineering, JNTUHCEH, Hyderabad, Telangana, India. This volume contains papers mainly focused on data mining, wireless sensor networks, parallel computing, image processing, network security, MANETS, natural language processing, and internet of things.